Helminths of toad Rhinella icterica (Bufonidae), from the municipality of Botucatu, São Paulo State, Brazil. - Pinhao, Rebeca; Wunderlich, Alison Carlos; Alves dos Anjos, Luciano; da Silva, Reinaldo Jose (My University, 2009)
Fifteen specimens of bufonid toad Rhinella icterica (Spix, 1824), 7 males and 8 females, collected in the municipality of Botucatu, São Paulo State, Brazil, from March 2002 to January 2003, were examined for helminth parasites. All toads were infected with at least one parasite species (overall prevalence = 100%). Five helminth species were found, including four nematode species, Rhabdias fuelleborni Travassos, 1926, Oswaldocruzia subauricularis (Rudolphi, 1819), gen. sp. no identified Cosmocercidae Travassos, 1925 and larvae of Physaloptera Rudolphi, 1819, and one acanthocephalan species, Acanthocephalus saopaulensis Smales, 2007. Rhabdias fuelleborni and A. saopaulensis were the most abundant species. Except for Physalopteridae larvae, all helminths occur in high prevalence (> 70%). All helminth species presented a distribution toward to more aggregated pattern in these host samples.